Evaluación de beauveria bassiana a partir de un cultivo monoespórico para el control de gusano blanco de la papa (premnotrypes vorax) en condiciones de Laboratorio Campus Salache 2022. - Caillagua Tayo, Kateryn Lisbeth (2022)
The white worm affects the potato crop in the larval stage to the tuber, causing production losses between fifty and sixty percent, for this reason the purpose of this research was to determine the best concentration for the control of Premnotrypes vorax and identify the best substrate during the research process. The study was conducted in the microbiology laboratory of the Technical University of Cotopaxi. The research process consisted of some phases: multiplication, elaboration, counting of conidia to determine concentrations and the last phase consisted of the application of the concentration of Beauveria bassiana in the experimental units. The experimental design was an additional AxB+1 factorial arrangement with four repetitions, where Factor A corresponds to the concentrations of conidia (〖10〗^8, 〖10〗^9, 〖10〗^10 conidia /ml), Factor B corresponds to the substrates (sterilized - not sterilized), obtaining a total of 28 experimental units with 15 larvae for each experimental unit. The variable in the study was the percentage of mortality to perform the results, a program called Infostat was used and when obtaining the ADEVA with the statistically significant results, the Tukey test was applied to 5% to obtain the different ranges of significance. The result for the percentage of mortality was determined that the T6 treatment (concentration 〖10〗^10 conidia /ml with unsterilized substrate) with a higher percentage of 100%, being the best compared to the additional one that did not present dead larvae, followed by the T5 Treatment (sterilized with concentration 〖10〗^10 conidia /ml with a percentage of 91.5%. Therefore, it is concluded that the best concentration was 〖10〗^10 conidia /ml to control the larva of Premnotrypes vorax, in addition to the fact that in the substrate there was no significant difference between the substrates (sterile and non-sterile) for the control of the white potato worm, thus it was shown that Beauveria bassiana does not depend on the substrate.